PENDELEGASIAN TUGAS KEPADA TRAINEE DI MAIN KITCHEN GRAND ROYAL PANGHEGAR HOTEL BANDUNG - Asep Rijwan; Rian Andriani (Jurnal Pariwisata, 2014)
Abstract - The problem is how to meticulous the delegation’s task to the trainee in the Main Kitchen, how the standard operational prosedure for the delegation of task to the trainees in the main kitchen, as well as how chance and opportunity from the delegation of the task to the trainee in the Main Kitchen. In terms of data processing, the author uses descriptive analysis, the methods that attempt to collect data and in accordance with the actual circumstances, present and analysis and than can give you a pratty clear picture of the object being examined and than take his conclution. Based on the results observation it can be inferred that the delegation of task to the trainee in the Main Kitchen of the Grand Royal Panghegar was implemented very well, it can bee seen with pretty clear delegation the task of properly licensed by the trainees. Standard operational prosedure of the delegation to the trainees in the Main Kitchen of the Grand Royal Panghegar Hotel is good, it can bee seen that the trainees can perform activities in the main kitchen with good anyway. The chances of the delegation of the task to the trainee in Main Kitchen of the Grand Royal Panghegar Hotel makes the trainees more confidence, have new experiences in food processing, futher increasing the skill of the trainees, and and have the knowladge that more than ever, and staff were not going to get too much of the burden work, sice most can be done by tranees with good. Base on the resoults of observation and discution, the authors conclude that when standard operational prosedures by delegation to trainees run well, then in addition to impact both to trainees will impact both to staff or to staff or the hotel it self. Abstrak - Masalah yang di teliti adalah bagaimana pendelegasian tugas kepadatraineedi main kitchen, bagaimana standar operasional prosedur pendelegasian tugas kepada trainee di main kitchen, serta bagaimana kesempatan dan peluang dari pendelegasian tugas kepada trainee di main kitchen.  Dalam hal pengolahan data, penulis menggunakan analisis deskriptif, yaitu metode yang berusaha mengumpulkan data dan sesuai dengan keadaan yang sebenarnya, menyajikan serta menganalisanya sehigga dapat memberikan gambaran yang cukup jelas atas objek yang diteliti dan kemudian di ambil kesimpulannya. Berdasarkan hasil observasi ini dapat disimpulkan bahwa pendelegasian tugas kepada trainee di Main Kitchen Grand Royal Panghegar Hotel sudah dilaksanakan dengan sangat baik, hal ini dapat dilihat dengan di selesaikannya delegasi tugas dengan baik pula oleh trainee. Standar operasional prosedur pendelegasian kepada trainee di Main Kitchen Grand Royal Panghegar Hotel sudah baik, hal ini dapat dilihat bahwa trainee dapat melaksanakan kegiatan- kegiatan yang ada di main kitchen dengan baik pula. Peluang dari pendelegasian tugas kepada trainee di Main Kitchen Grand Royal Panghegar Hotel menjadikan trainee lebih percaya diri, memiliki pengalaman baru dalam mengolah makanan, lebih meningkatnya skill trainee, dan memiliki pengetahuan yang lebih dari sebelumnya, dan staff pun tidak akan mendapat terlalu banyak beban pekerjaan, karena sebagian dapat dikerjakan oleh trainee dengan baik. Berdasarkan dari hasil observasi dan pembahasan tersebut, penulis menyimpulkan bahwa apabila standar operasional prosedur pendelegasian kepada Trainee dijalankan dengan baik, maka selain berdampak baik kepada trainee akan berdampak baik pula kepada staff atau hotel itu sendiri.